Macrophage Apoptosis in Advanced Atherosclerosis - Tabas, Ira (2009)
Plaque necrosis in advanced atheromata, which triggers acute atherothrombotic vascular events, is caused by the apoptosis of lesional macrophages coupled with defective phagocytic clearance of the dead cells. The central enabling event in macrophage apoptosis relevant to advanced atherosclerosis is the unfolded protein response (UPR), an endoplasmic reticulum (ER) stress pathway. The UPR effector CHOP (GADD153) amplifies release of ER Ca(2+) stores, which activates a central integrator of apoptosis signaling, calcium/calmodulin-dependent protein kinase II (CaMKII). CaMKII, in turn, leads to activation of pro-apoptotic STAT1, induction of the death receptor Fas, and stimulation of the mitochondria-cytochrome c pathway of apoptosis. While these pathways are necessary for apoptosis, apoptosis occurs only when the cells are also exposed to one or more additional “hits.” These hits amplify pro-apoptotic pathways and/or suppress compensatory cell-survival pathways. A second hit relevant to atherosclerosis is activation of pattern recognition receptors (PRRs), such as scavenger and toll-like receptors. In vivo relevance is suggested by the fact that advanced human lesions express markers of UPR activation that correlate closely with the degree of plaque vulnerability and macrophage apoptosis. Moreover, studies with genetically altered mice have shown that ER stress and PRR activation are causative for advanced lesional macrophage apoptosis and plaque necrosis. In summary, a key cellular event in the conversion of benign to vulnerable atherosclerotic plaques is ER stress-induced macrophage apoptosis. Further understanding of the mechanisms and consequences of this event may lead to novel therapies directed at preventing the clinical progression of atheromata.